Principles of electrodynamics - Schwartz, Melvin, 1932-2006 (Dover Publications, 1987)
This advanced undergraduate- and graduate-level text by the 1988 Nobel Prize winner establishes the subject's mathematical background, reviews the principles of electrostatics, then introduces Einstein's special theory of relativity and applies it throughout the book in topics ranging from Gauss' theorem and Coulomb's law to electric and magnetic susceptibility.
"... unabridged, corrected republication of the work first published by the McGraw-Hill Book Company, New York, 1972, in its International series in pure and applied physics"--T.p. verso.
Includes index.
Keywords: Electrodynamics.; elektronické knihy; electronic books